Hubungan Response Time Perawat dengan Kepuasan Pasien di IGD RSU Islam Harapan Anda Kota Tegal - Nurul Muzamil; Dwi Retno Sulistyaningsih; Erna Melastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Nurses’ response time is a crucial indicator of service quality in the Emergency Department (ED). A prompt response not only plays a vital role in ensuring patient safety but also significantly affects patient satisfaction with the care received. Patient satisfaction in the ED is often considered a benchmark of hospital quality, as the ED operates 24/7 and frequently deals with critical conditions. This study aimed to determine the relationship between nurses’ response time and patient satisfaction in the ED of Harapan Anda Islamic General Hospital, Tegal. This study employed an observational analytic design with a cross-sectional approach. A total of 92 ED patients were included as samples based on inclusion criteria. Nurses’ response time was measured using a stopwatch, starting from the completion of triage until the first contact with the nurse. Patient satisfaction was assessed using the standardized Brief Emergency Department Patient Satisfaction Scale (BEPSS) questionnaire. Data analysis was conducted using Pearson’s Chi-Square test to examine the relationship between the two variables. The results showed that 75 patients (81.5%) experienced a fast response time, while 72 patients (78.3%) reported being satisfied with the care provided. Statistical analysis yielded a Pearson’s Chi-Square value of 11.933, with an odds ratio of 6.545 and a significance level of 0.001 (p < 0.05). These findings indicate a significant association between nurses’ response time and patient satisfaction. In conclusion, nurses’ response time is strongly related to patient satisfaction in the ED of Harapan Anda Islamic General Hospital. Other factors such as effective communication, clinical competence, ED environment, and triage system may also influence satisfaction and should be considered in future studies.